Toda and Yamamoto Causality Between Stock Market Development and Economic Growth: Evidence from China, Japan, Singapore, UK and US - Zhang, Haoxing (2012)
This study investigates the direction of the causality between economic growth and stock market performance in three Asian countries - China, Singapore, Japan and two western developed countries - the UK and the US. By analyzing the quarterly real GDP and the stock index in each country with the help of Augmented Dickey-Fuller (ADF) unit root test, Breusch-Godfrey LM test, Johansen co-integration test and a subsequent improved version of traditional Granger-causality test proposed by Toda and Yamamoto (1995), we find that there is no long-run co-integrating relationship between quarterly real GDP and stock market index in all five countries. Additionally, evidences are presented of unidirectional causality running from stock market development to economic growth in all three Asian countries and bidirectional causality in the United States. However, the FTSE 100 and the quarterly real GDP in the United Kingdom is proved to be independent. Therefore, the causal relationship between stock market performance and economic growth in the three Asian countries support the “supply-leading” hypothesis proposed by Patrick (1966).